2015
DOI: 10.1371/journal.pone.0123688
|View full text |Cite|
|
Sign up to set email alerts
|

Trend and Risk Factors of Diverticulosis in Japan: Age, Gender, and Lifestyle/Metabolic-Related Factors May Cooperatively Affect on the Colorectal Diverticula Formation

Abstract: BackgroundDespite the marked increase of diverticulosis, its risk factors have not been adequately elucidated. We therefore aim to identify significantly associated factors with diverticulosis. We also aim to investigate the present state of diverticulosis in Japan.MethodsWe reviewed the medical records from 1990 to 2010 that included the data of consecutive 62,503 asymptomatic colonoscopy examinees from the general population in Japan. Most recent 3,327 examinees were analyzed with 16 background factors.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
5
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 43 publications
11
85
5
5
Order By: Relevance
“…Another study of individuals with a mean age of 55 years showed the prevalence of diverticula was 42% [26]. According to statistics published during 2001-2010 in Japan, the prevalence of colonic diverticula in individuals with a mean age of 52 years was 23.9% [2]. These findings indicate that the proportion of individuals with colonic diverticula is lower in Japan than that in the West.…”
Section: Epidemiology Of Diverticula In the Colonmentioning
confidence: 93%
See 2 more Smart Citations
“…Another study of individuals with a mean age of 55 years showed the prevalence of diverticula was 42% [26]. According to statistics published during 2001-2010 in Japan, the prevalence of colonic diverticula in individuals with a mean age of 52 years was 23.9% [2]. These findings indicate that the proportion of individuals with colonic diverticula is lower in Japan than that in the West.…”
Section: Epidemiology Of Diverticula In the Colonmentioning
confidence: 93%
“…However, the incidence of colonic diverticula on the left side increases with age to the point where 60% of patients aged ≥70 years have diverticula on the left side of the colon, with 25% of these patients having colonic diverticula only on the left side of the colon [2,27,28]. In the United States, 80% of colonic diverticula occur on the left side including 70% occurring in the sigmoid colon, which account for the majority of colonic diverticula.…”
Section: Cq2: Does the Frequency Of Colonic Diverticula Vary By Site mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum anti-H. pylori IgG, serum pepsinogen I and II, and other factors Serum anti-H. pylori IgG and pepsinogens were measured using commercial kits (E-plate; EIKEN, Tokyo, Japan) [26][27][28][29][30]. According to the manufacturer's instructions, a titer of anti-H. pylori IgG C10 U/ml was considered as positive for H. pylori infection.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The prevalence of colonic diverticulosis is increasing in Western and Asian countries [1][2][3]. Diverticular disease is defined as clinically significant and symptomatic diverticulosis complicated by diverticulitis, diverticular bleeding, segmental colitis associated with diverticula, or symptomatic uncomplicated diverticular disease; these DOI: 10.1159/000492178 are the so-called complications of colonic diverticulosis.…”
Section: Introductionmentioning
confidence: 99%